2014
DOI: 10.1021/bm500902t
|View full text |Cite
|
Sign up to set email alerts
|

Postpolymerization Modification Using Less Cytotoxic Activated Ester Polymers for the Synthesis of Biological Active Polymers

Abstract: Activated ester polymers, pioneered by Ferruti and Ringsdorf in the 1970s, are attractive polymeric materials because they can easily be converted into functional polymers by reacting with amine nucleophiles. In the present study, methyl salicylate acrylate, salicyl acrylate, and tert-butyl salicylate acrylate monomers were polymerized yielding three novel reactive precursors suitable for the postpolymerization modification with primary and secondary amines. The reactivities of poly(pentafluorophenyl acrylate)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 40 publications
0
46
0
Order By: Relevance
“…As reported in our previous study [25], PFPA has a much higher reactivity towards hexylamine than methyl salicylate acrylate [25]. This motivated us to further explore the reactivity difference of these two esters.…”
Section: Resultsmentioning
confidence: 63%
See 4 more Smart Citations
“…As reported in our previous study [25], PFPA has a much higher reactivity towards hexylamine than methyl salicylate acrylate [25]. This motivated us to further explore the reactivity difference of these two esters.…”
Section: Resultsmentioning
confidence: 63%
“…Our previous work also demonstrated that the reactivity of PFPA ester is higher than activated esters derived from salicylate derivatives [25]. These positive features motivated us to investigate the difference in amine reactivity, especially aliphatic amines, between PFPA and methyl salicylate acrylate.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations